Anion‐Vacancy‐Defect Passivation of a 2D‐Layered Tin‐Based Perovskite Thin‐Film Transistor with Sulfur Doping - Jae‐Hyeok Cho; Ji‐Young Go; Tan Tan Bui; Seunguk Mun; Yunseok Kim; Kyunghan Ahn; Yong‐Young Noh; Myung‐Gil Kim (Advanced Electronic Materials, 2023)
Abstract Metal halide perovskites have attracted a considerable amount of research attention with significant progress made in the field of optoelectronics. Despite their outstanding electrical characteristics, structural defects impede their potential performance due to the polycrystalline nature of solution‐processed perovskite films. Herein, the effective p‐type doping and defect passivation of phenethylammonium tin iodide ((PEA)2SnI4) perovskite films using xanthate additives as a sulfur source is reported. Sulfur can be introduced to the iodine vacancies mainly at the grain boundaries of the perovskite film, passivating the electrical defects originating from the iodine vacancy and increasing the hole concentration. The Fermi‐level shift toward the valence band maximum of the sulfur‐doped perovskite film is confirmed using ultraviolet photoemission spectroscopy, resulting in p‐type doping. Finally, the electrical performance improvement for the 0.2% sulfur‐doped (PEA)2SnI4 thin‐film transistor with a mobility of 1.45 cm2 V−1 s−1, an on/off ratio of 2.9 × 105 is demonstrated, and hysteresis of 10 V is reduced.